Social and emotional deprivation in the mother is associated with anatomical and functional alterations in the fetus and newborn - Pacora, Percy (2005)
Objective: To ascertain that social and emotional deprivation of the mother is associated with fetal growth restriction, fetal death, preterm birth and congenital defects. Materials and Methods: We retrieved the maternal and perinatal outcome from the Informatic Perinatal System of all pregnancies with antenatal care whose delivery occurred between January 1, 1992 and December 31, 2001. Three groups of patients with social and emotional deprivation were included: 1) single women (n=1285), 2) teenage women with absent prenatal care (APC), (n=2131), and 3) primigravid with stature lower than 160 cm (n=35722). Maternal and perinatal outcome were compared with: 1) women living with sexual partner (n=5550), 2) teenage women with prenatal care (n=7644), and 3) primigravids taller than 159 cm (n=5264). Odds ratio and 95% confidence interval (CI) were calculated. Results: Single women presented greater risk of placental failure (OR 1,92, 95%CI 1,51-2,44), fetal growth restriction (OR 2,02, 95%CI 1,45-2,82), and premature rupture of fetal membrane (OR 1,28, 95%CI 1,00-1,63) as compared with women living with sexual partners. Teenagers presented greater risk of fetal death (OR 2,89, 95%CI 1,85- 4,50), premature rupture of fetal membranes (OR 1,38, 95%CI 1,18-1,62), preterm labor (OR 1,63, 95%CI 1,39- 1,91), small for gestational age infant (OR 1,25, 95%CI 1,08-1,44), neonatal morbidity (OR 1,23, IC95% 1,07- 1,41), perinatal asphyxia (OR 2,73, 95%CI 1,33-5,58), low one minute Apgar score (OR 1,26, 95%CI 1,05-1,52), respiratory distress syndrome (OR 1,51, 95%CI 1,10-2,06), neonatal sepsis (OR 1,54, 95%CI 1,19-1,99), prematurity (OR 1,50, 95%CI 1,27-1,78), neonatal death (OR 2,56, 95%CI 1,88-3,48), and perinatal death (OR 3,02, 95%CI 2,24-4,07) as compared with teen-age women without absent prenatal care. Primigravids shorter than 160 cm presented greater risk of absent prenatal care (OR 1,22, 95%CI 1,13- 1,32), preterm labor (OR 1,12, 95%CI 1,00-1,26), fetopelvic disproportion (OR 1,49, 95%CI 1,11-2,02), cesarean section delivery (OR 1,28, 95%CI 1,19-1,38), low one minute Apgar score (OR 1,20, 95%CI 1,07-1,35), small for gestational age infant (OR 1,29, 95%CI 1,17-1,42), and preterm neonate (OR 1,12, 95%CI 1,00-1,26) as compared to primigravids with taller than 159 cm. Conclusions: Women with social and/or emotional privation, such as single pregnant women, teenage pregnant women with no prenatal care and women with low stature, are at increased perinatal risk of anatomical and functional alterations in the fetus and newborn.